KEMISKINAN DI WILAYAH PEDESAAN NTB : STUDI KASUS WANITA PEMBUAT GARAM DI DUSUN MEDANG - Maryadi Maryadi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2002)
Role of women in development has been well-known. Women roles in rural area can be identified from their involvement in rural industries either agricultural home industries or other small-scale industries processing material taken from natural resources. One of such natural resource materials is sea water to be further processed as salts. Most of women in Medang Hamlet, Village of Sekotong Barat, Nusa Tenggara Barat Province work as salt makers. Instead of drying salty water by using sunshine, the salt farmers in Medang Hamlet use wood in heating the salt water. The study finds that the income earned from this activity is considerably low. Since there is no other source of income alternative for the women in this hamlet, making salt becomes the only job that can be done. The consequence is that the villagers in this area are still live under poverty line.